KEKOHESIFAN KELOMPOK SEBAGAI PEMODERASI PENGARUH INFORMASI ASIMETRI PADA KESENJANGAN ANGGARAN - Derti, Ni Kadek Medha; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi; Vol 18 No 3 (2017), 2017)
Participationbudget is a budgeting technique that is most ideal, but many researchers explained that budgetary participation influence the budget gap. With the budget gap, the performance will look good for being able to achieve revenue targets and capable of pressing charges under budget figures, but the actual performance is not optimal for the realization of the actual achievement and the realization of cost is already over budget. This study aims to provide additional empirical evidence regarding the "group cohesiveness as a moderating Effect of Information Asymmetry on Budget Gaps". The research sample consisted of 80 respondents. Methods of data collection using questionnaires. Data analysis techniques used are: simple linear regression, and regression moderation. Based on the results of analysis show that information asymmetry positive effect on the budget gap. Interaction between Information Asymmetry with group cohesiveness is able to strengthen the influence of Information Asymmetry on Budget Gaps.
Keywords: Information Asymmetry, Group Cohesiveness, Budgetary Slack